Preparation method of flaky copper powder and flaky copper powder

By adding antioxidants before and after the ball mill and performing pickling treatment, the oxidation problem of sheet copper powder is solved, the conductivity and applicability are improved, and it is suitable for large-scale industrial production.

CN119259997APending Publication Date: 2025-01-07SUZHOU XINGHAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478640.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing physical preparation methods are prone to oxidation when preparing sheet copper powder, resulting in poor conductivity, and the preparation method is cumbersome and not suitable for large-scale industrial production.

Method used

Antioxidants were added before and into the ball mill, and the mixture was formed by stirring and ball milling, and the surface oxide was removed during the ball milling process, and finally the sheet copper powder was prepared by drying.

Benefits of technology

The antioxidant ability of copper powder is improved, and the prepared sheet copper powder has good conductivity and small resistance, which is suitable for large-scale industrial production. Sodium hypophosphite is used as an antioxidant to pollute the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259997A_ABST
    Figure CN119259997A_ABST
Patent Text Reader

Abstract

The invention discloses a flaky copper powder preparation method and flaky copper powder.The flaky copper powder preparation method comprises the following steps that under the stirring condition, spherical copper powder, an antioxidant A and a grinding aid are dispersed in a solvent, and a mixed solution is obtained; zirconium beads are added into the obtained mixed solution for ball milling treatment, the antioxidant B is added again in the ball milling process, and a solid phase is obtained; the obtained solid phase is washed and dried, and flaky copper powder is obtained; according to the preparation method, the flaky copper powder is prepared through a physical preparation method, the antioxidant is added twice before ball milling and during ball milling, the oxidation resistance of the copper powder can be effectively improved, the spherical copper powder, the antioxidant and the grinding aid are dissolved in the solvent to form the mixed solution, the risk that the spherical copper powder is oxidized due to exposure in air can be effectively reduced, and the service life of the spherical copper powder is prolonged. And finally, a solid phase obtained after ball milling is subjected to acid pickling to be used for removing surface oxides, and the prepared flaky copper powder is high in oxidation resistance, good in flaky effect, smooth in surface, good in conductivity, small in resistance and small in environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic paste, and in particular to a preparation method of flaky copper powder and the flaky copper powder. Background Art

[0002] With the development of electronic technology, conductive coatings and electronic pastes are increasingly used in the electronics industry. Flake silver powder is used as a conductive filler in large quantities. However, silver ions are prone to migration under hot and humid conditions, which leads to increased coating resistance and decreased performance. In addition, silver is relatively expensive. The conductivity of copper is similar to that of silver, and it is cheap, making it an ideal substitute for silver. Spherical copper powder is mainly point contact, while flake copper powder is mainly surface contact, which is conducive to the conduction of charge, making flake copper powder have better conductivity. The preparation of flake copper powder generally includes two categories: physical preparation method and chemical preparation method. Among them, the physical preparation method has significant application value in large-scale industrial production due to its relatively simplified preparation process and low cost advantages.

[0003] At present, the existing physical preparation method has some challenges in preparing flaky copper powder. Specifically, the copper powder prepared by this method is often prone to oxidation, resulting in poor conductivity, thus affecting the quality and application performance of the copper powder. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing flaky copper powder and flaky copper powder, which solves the problems of poor antioxidant ability, poor conductivity, poor sheeting effect, complicated preparation method and difficulty in large-scale industrial production in the existing preparation method.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing flaky copper powder comprises the following steps:

[0007] S1, dispersing spherical copper powder, antioxidant A and grinding aid in a solvent under stirring conditions to obtain a mixed solution;

[0008] S2, adding zirconium beads to the mixed solution obtained in step S1 for ball milling, and adding antioxidant B again during the ball milling process to obtain a solid phase;

[0009] S3, washing and drying the solid phase obtained in step S2 to obtain flaky copper powder.

[0010] Furthermore, the solvent is one or two of propylene glycol, diethylene glycol ethyl ether, and ethylene glycol butyl ether, and the mass ratio of the spherical copper powder to the solvent is 1:(1-2).

[0011] Furthermore, the grinding aid is polyvinyl pyrrolidone, sodium citrate, tartaric acid, and adipic acid, and the mass ratio of the spherical copper powder to the grinding aid is 1:(0.5-3).

[0012] Furthermore, the antioxidant A in step S1 is sodium hypophosphite, and the antioxidant B in step S2 is sodium hypophosphite.

[0013] Further, in step S1, the mass ratio of the spherical copper powder to the antioxidant A is 1:(0.04-0.08);

[0014] In step S2, the mass ratio of the spherical copper powder to the antioxidant A is 1:(0.02-0.06). Furthermore, the zirconium beads are zirconium oxide balls, the average particle size of the zirconium beads is 0.5-1.5 mm, and the mass ratio of the copper powder to the zirconium beads is: 1:(1-10).

[0015] Furthermore, the ball milling treatment in step S2 includes setting the ball mill speed to 100-600 rpm and the ball milling time to 0.5-6 h.

[0016] Furthermore, step S3 washing includes sequentially acid washing, water washing, and alcohol washing of the solid phase after solid-liquid separation, wherein the acid used for the acid washing is sulfuric acid, and the mass ratio of copper powder to sulfuric acid is 1:(0.04-0.1), and the sulfuric acid is dissolved in deionized water, and the mass ratio of copper powder to deionized water is 1:10.

[0017] Furthermore, in step S3, the drying temperature is 45-60° C., and the drying time is 8 hours.

[0018] The present invention also provides flaky copper powder prepared by the flaky copper powder preparation method. The flaky copper powder has a resistivity of 0.000041327-0.000627913 Ω·cm, a particle size of 3-10 μm, and a thickness of 0.5-1.5 μm.

[0019] In summary, this application has the following beneficial effects:

[0020] 1. The method of the present application can effectively inhibit the oxidation of copper powder in the early stage by adding an antioxidant twice before and during ball milling, and can also avoid the situation where the solution temperature increases due to long-term ball milling, resulting in the aggravation of the oxidation effect of copper powder, thereby improving the antioxidant capacity of copper powder. The prepared flaky copper powder has good flake effect, good conductivity, and low resistance. Sodium hypophosphite is selected as an antioxidant, which has little pollution to the environment.

[0021] 2. The method of the present application can effectively reduce the risk of oxidation of the spherical copper powder due to exposure to air by first dissolving the spherical copper powder, antioxidant and grinding aid in a solvent to form a mixed solution, and finally pickling the solid phase after ball milling to remove surface oxides. The prepared flaky copper powder has a smooth surface, good conductivity and low resistance;

[0022] 3. The method of the present application prepares flaky copper powder by a physical preparation method, which is simple and easy to be mass-produced industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope image of the flaky copper powder obtained in Example 1;

[0024] Figure 2 is a scanning electron microscope image of the flaky copper powder obtained in Example 2;

[0025] Figure 3 This is a scanning electron microscope image of the flaky copper powder obtained in Comparative Example 2. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] Step 1: Prepare a mixed solution: weigh 500 g of spherical copper powder, 30 g of sodium hypophosphite, and 500 g of polyvinyl pyrrolidone, respectively, and disperse them in 750 g of propylene glycol, and stir for 30 min;

[0029] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 1500g of zirconia balls with a particle size of 1mm and add them to the ball mill for ball milling. The speed of the ball mill is set to 200rmp. After ball milling for 1h, weigh 20g of sodium hypophosphite and add it to the mixed solution. Continue ball milling for 1h. After the ball milling is completed, use deionized water to separate the zirconia balls and copper powder to obtain a solid phase;

[0030] Step 3: Prepare dilute sulfuric acid: Dissolve 25g of sulfuric acid in 5000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water to wash repeatedly 3 times, then wash twice with anhydrous ethanol, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 50°C and dry for 8h to obtain flaky copper powder; the scanning electron microscope image of the obtained flaky copper powder is as follows Figure 1 shown.

[0031] Example 2

[0032] Step 1: Prepare a mixed solution: weigh 300 g of spherical copper powder, 15 g of sodium hypophosphite, and 150 g of sodium citrate, respectively, disperse them in 300 g of diethylene glycol ethyl ether, and stir for 30 min;

[0033] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 300 g of zirconia balls with a particle size of 0.5 mm and add them to the ball mill for ball milling. The speed of the ball mill is set to 300 rpm. After ball milling for 0.5 h, weigh 15 g of sodium hypophosphite and add it to the mixed solution. Continue ball milling for 0.5 h. After the ball milling is completed, use deionized water to separate the zirconia balls and copper powder to obtain a solid phase.

[0034] Step 3: Prepare dilute sulfuric acid: Dissolve 12g of sulfuric acid in 3000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water to wash repeatedly 3 times, then wash twice with anhydrous ethanol, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 45°C and dry for 8h to obtain flaky copper powder; the scanning electron microscope image of the obtained flaky copper powder is as follows Figure 2 shown.

[0035] Example 3

[0036] Step 1: Prepare a mixed solution: weigh 800 g of spherical copper powder, 32 g of sodium hypophosphite, and 1600 g of tartaric acid, respectively, disperse them in 1600 g of ethylene glycol butyl ether, and stir for 30 min;

[0037] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 4800g of zirconia balls with a particle size of 1.5mm and add them to the ball mill for ball milling. The speed of the ball mill is set to 500rmp. After ball milling for 2h, weigh 48g of sodium hypophosphite and add it to the mixed solution. Continue ball milling for 2h. After the ball milling is completed, use deionized water to separate the zirconia balls and copper powder to obtain a solid phase;

[0038] Step 3: Prepare dilute sulfuric acid: dissolve 80g of sulfuric acid in 8000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water and wash repeatedly for 3 times, then wash twice with anhydrous ethanol, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 55°C and dry for 8h to obtain flaky copper powder.

[0039] Example 4

[0040] Step 1: Prepare a mixed solution: weigh 1000g of spherical copper powder, 70g of sodium hypophosphite, and 3000g of adipic acid, respectively, and disperse them in 1500g of propylene glycol, and stir for 30min;

[0041] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 7000g of zirconia balls with a particle size of 1mm and add them to the ball mill for ball milling. The speed of the ball mill is set to 600rmp. After ball milling for 3h, weigh 30g of sodium hypophosphite and add it to the mixed solution. Continue ball milling for 3h. After the ball milling is completed, use deionized water to separate the zirconia balls and copper powder to obtain a solid phase;

[0042] Step 3: Prepare dilute sulfuric acid: dissolve 70g of sulfuric acid in 10000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water and wash repeatedly for 3 times, then wash twice with anhydrous ethanol, pour out the supernatant, and put the obtained precipitate into a vacuum oven at 60°C and dry for 8h to obtain flaky copper powder.

[0043] Comparative Example 1

[0044] The preparation method of this comparative example is the same as that of Example 1 except that sodium hypophosphite is not added during the preparation:

[0045] Step 1: Prepare a mixed solution: weigh 500 g of spherical copper powder and 500 g of polyvinyl pyrrolidone respectively, disperse them in 750 g of propylene glycol, and stir for 30 min;

[0046] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 1500 g of zirconia balls with a particle size of 1 mm and add them to the ball mill for ball milling. The ball mill speed is set to 200 rpm and the ball milling time is 2 h. After the ball milling is completed, the zirconia balls and copper powder are separated with deionized water to obtain a solid phase;

[0047] Step 3: Prepare dilute sulfuric acid: dissolve 25g of sulfuric acid in 5000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water to wash repeatedly for 3 times, then wash with anhydrous ethanol twice, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 50°C and dry for 8h to obtain flaky copper powder; sodium hypophosphite is not added as an antioxidant, which causes the copper powder to be easily oxidized during the preparation process. The formation of copper oxide will form one or more oxide films on the surface of the copper powder. These oxide films are usually harder and more brittle than copper itself, which will increase the roughness of the copper powder surface. During the oxidation process, the copper powder particles will agglomerate due to the bridging effect of the oxide film, affecting the particle size distribution of the copper powder, and the flake effect is not good.

[0048] Comparative Example 2

[0049] The preparation method of this comparative example is the same as that of Example 1 except that sodium hypophosphite is not added in batches during the preparation, but is added once only when the mixed solution is prepared:

[0050] Step 1: Prepare a mixed solution: weigh 500 g of spherical copper powder, 50 g of sodium hypophosphite, and 500 g of polyvinyl pyrrolidone, respectively, and disperse them in 750 g of propylene glycol, and stir for 30 min;

[0051] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 1500 g of zirconia balls with a particle size of 1 mm and add them to the ball mill for ball milling. The ball mill speed is set to 200 rpm and the ball milling time is 2 h. After the ball milling is completed, the zirconia balls and copper powder are separated with deionized water to obtain a solid phase;

[0052] Step 3: Prepare dilute sulfuric acid: Dissolve 25g of sulfuric acid in 5000g of deionized water, stir ultrasonically for 40min, pour out the supernatant after pickling, add deionized water to wash repeatedly 3 times, then wash twice with anhydrous ethanol, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 50°C and dry for 8h to obtain flaky copper powder; Figure 3 As shown, sodium hypophosphite is not added in batches during the preparation process, but is only added when the mixed solution is prepared. The spherical copper powder will gradually break up during the ball milling process, and the surface in contact with the mixed solution formed by the breakup will gradually increase. Although the oxidation of the copper powder can be effectively inhibited in the early stage, the temperature of the mixed solution will increase due to long-term ball milling, which will intensify the oxidation effect of the copper powder. In addition, the surface in contact with the mixed solution will increase in the later stage, and the required antioxidant will be insufficient, which will make the copper powder easy to oxidize, resulting in uneven particle size distribution, poor flaking effect, and rough surface.

[0053] Comparative Example 3

[0054] The preparation method of this comparative example is the same as that of Example 1 except that pickling is not performed during the preparation:

[0055] Step 1: Prepare a mixed solution: weigh 500 g of spherical copper powder, 30 g of sodium hypophosphite, and 500 g of polyvinyl pyrrolidone, respectively, and disperse them in 750 g of propylene glycol, and stir for 30 min;

[0056] Step 2: Transfer the mixed solution prepared in step 1 to a ball mill, and weigh 1500g of zirconia balls with a particle size of 1mm and add them to the ball mill for ball milling. The speed of the ball mill is set to 200rmp. After ball milling for 1h, weigh 20g of sodium hypophosphite and add it to the mixed solution. Continue ball milling for 1h. After the ball milling is completed, use deionized water to separate the zirconia balls and copper powder to obtain a solid phase;

[0057] Step 3: Add deionized water to the solid phase obtained in step 2 and wash it repeatedly for 3 times, then wash it with anhydrous ethanol for 2 times, pour out the supernatant, and put the obtained precipitate into a vacuum oven at a temperature of 50°C and dry it for 8 hours to obtain flaky copper powder; if acid washing is not performed, the surface oxide formed during the preparation process cannot be removed, affecting the flake effect of the copper powder.

[0058] The particle morphology, thickness, particle size distribution range, resistivity, and product surface smoothness of the products of Examples 1-4 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1, wherein the particle morphology of the product was measured by SEM electron microscope scanning, the particle size distribution was measured by a laser particle size analyzer, and the resistivity was measured by a powder resistivity tester.

[0059] Table 1

[0060]

[0061]

[0062] It should be understood that the preferred specific embodiments of the present invention can be modified and varied by ordinary technicians in the field without creative work. Therefore, any technical solution that can be obtained by technicians in the field of technology through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing flaky copper powder, characterized in that: The steps include: S1, dispersing spherical copper powder, antioxidant A and grinding aid in a solvent under stirring conditions to obtain a mixed solution; S2, adding zirconium beads to the mixed solution obtained in step S1 for ball milling, and adding antioxidant B again during the ball milling process to obtain a solid phase; S3, washing and drying the solid phase obtained in step S2 to obtain flaky copper powder.

2. The method for preparing flaky copper powder according to claim 1, characterized in that: The solvent is one or two of propylene glycol, diethylene glycol ethyl ether, and ethylene glycol butyl ether, and the mass ratio of the spherical copper powder to the solvent is 1:(1-2).

3. The method for preparing flaky copper powder according to claim 1, characterized in that: The grinding aids are polyvinyl pyrrolidone, sodium citrate, tartaric acid and adipic acid, and the mass ratio of the spherical copper powder to the grinding aids is 1:(0.5-3).

4. The method for preparing flaky copper powder according to claim 1, characterized in that: The antioxidant A in step S1 is sodium hypophosphite, and the antioxidant B in step S2 is sodium hypophosphite.

5. The method for preparing flaky copper powder according to claim 1, characterized in that: In step S1, the mass ratio of the spherical copper powder to the antioxidant A is 1:(0.04-0.08); In step S2, the mass ratio of the spherical copper powder to the antioxidant A is 1:(0.02-0.06).

6. The method for preparing flaky copper powder according to claim 1, characterized in that: The zirconium beads are zirconium oxide balls, the average particle size of the zirconium beads is 0.5-1.5 mm, and the mass ratio of the copper powder to the zirconium beads is: 1:(1-10).

7. The method for preparing flaky copper powder according to claim 1, characterized in that: The ball milling process in step S2 includes setting the ball mill speed to 100-600 rpm and the ball milling time to 0.5-6 h.

8. The method for preparing flaky copper powder according to claim 1, characterized in that: Step S3 washing includes sequentially acid washing, water washing, and alcohol washing of the solid phase after solid-liquid separation, wherein the acid used for the acid washing is sulfuric acid, and the mass ratio of copper powder to sulfuric acid is 1:(0.04-0.1), and the sulfuric acid is dissolved in deionized water, and the mass ratio of copper powder to deionized water is 1:

10.

9. The method for preparing flaky copper powder according to claim 1, characterized in that: The drying temperature in step S3 is 45-60° C. and the drying time is 8 hours.

10. A flaky copper powder obtained by the method for preparing a flaky copper powder according to any one of claims 1 to 9.